Transmission of recent shocks in a labour-DSGE model with wage rigidity - Meri Obstbaum; Sami Oinonen; Harri Pönkä; Juuso Vanhala; Lauri Vilmi (Bank of Finland, 2023)
In this paper we analyze features of the recent business cycle with a New Keynesian small open economy DSGE model with labour market frictions and wage rigidity. The model complements the existing analytical tools of the Bank of Finland by enabling detailed analysis of labour markets in a DSGE framework. We illustrate the properties of the model by presenting how recent shocks explain in flation and economic recovery in the euro area and Finland, with a specifi c emphasis on factors that are critical to explaining current labour market tightness.
URN:NBN:fi-fe2023042037970
Keywords: E24; E32; E37; F41; 330; DGSE model; labour market frictions; wage rigidity